Energy management system in industrial facilities (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
In a food company processes demand the use of a large amount of energy, that is why every saving opportunity counts and can not be wasted in the least, since this is reflected directly in the final cost of the product. For this reason, this research work centers its purpose in designing an energy management system for a sausage food company, in order to guide energy consumption more effectively and efficiently. For this, mainly in the company, a diagnosis was made in the electrical installations and all the necessary information related to the consumption of electrical energy was collected through an energy audit; In the same order of ideas, fundamental parameters were evaluated such as electrical energy consumed and production to then determine the consumption and energy efficiency indexes to design the energy management system, without affecting the productivity and comfort of the organization. Finally, the energy management system was established based on the continuous improvement framework Plan-Do-Check-Act (PDCA, acronym in English that correspond to "Plan-Do-Check-Act") which integrated the energy management in the good daily organizational practices through the analysis of the data collected during the diagnosis of electrical energy consumption, in addition, a series of recommendations are proposed that allow as much as possible the application of the system and reduce consumption through the application of new energy efficiency technologies.
Keywords: energy; savings; cost; system; management